Parlamentskii chas . Parlamentskii chas . Parliamentary Hour . Парламентский час - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Supreme Council of Russian Federation seminar on legal problems of economic reform; discussion of the budget deficit; asking Muscovites their opinions on Russia's current economic condition; People's Deputy IUrii Gekht attacked; the Moscow Artistic Academic Theater named after Gorky opens its 95th theater season. Featured in the program: Khasbulatov, Ruslan Imranovich (Chairman of the Supreme Soviet of the Russian Federation); Paramonova, Tat'iana (Economist); Doronina, Tat'iana Vasil'evna (Actress) Contributors: Berdnikova, Nina (Anchor) Семинар Верховного Совета Российской Федерации о правовых проблемах в условиях экономической реформы; обсуждение проблемы дефицита бюджета; опрос мнения москвичей о текущем экономическом положении России; нападение на народного депутата Юрия Гехта; МХАТ им. Горького открывает 951 театральный сезон. В программе участвуют: Хасбулатов, Руслан Имранович (Председатель Верховного Совета Российской Федерации); Парамонова, Татьяна (Экономист); Доронина, Татьяна Васильевна (Актриса) Создатели: Бердникова, Нина (Ведущий/Ведущая)